G501(P) A Kdm5c mutation and the diagnostic odyssey. (24th May 2017) - Seviar, D; Thomas, S; Hunt, D; Mercer, C; Williams, A; Temple, IK
Abstract : Aim: The 1 00 000 genomes project is sequencing the genomes of patients with rare diseases; we have sent over 1000 samples to the project to date. Our first result is from a child with intrauterine growth restriction and intellectual disability who has the Lysine(K)-specific demethylase 5C ( KDM5C ) variantc.769delC. We use this case report as an exemplar to illustrate the process in clinical practice. Methods: Through the 1 00 000 genomes project, whole-genome sequencing was completed from the child and his parents. To evaluate clinical relevance, the case was interpreted by i) the central project team; ii) the Genome Medicine Centre (GMC) pre- Review Board (clinical scientist and geneticist); iii) the GMC Rare Disease Board (Clinical genomics scientist, clinical geneticist, genetics counsellor, ethicist, technologist, referring clinician). Data discussed included in silico analysis, frequency in control populations, correlation with the clinical phenotype and investigation of the mutation phase within the family. Results: KDM5C is an epigenetic regulator, essential for neuronal survival and growth and causing X-linked intellectual disability. The mutation was a 'Tier 1' variant, i.e. a pathogenic variant within the phenotype-assigned-project-gene-panel (702 genes for ID; 88 for growth failure). The local review added that the mutation was absent from normal variant databases and that the mutation spectrum included truncating mutations 5' and 3' of c.769. The clinical phenotype was compatible with a KDM5C pathogenesis but not specific to it. Our MDT concluded that it was a 'class 4 variant', i.e. 'likely causative' of the child's disease. Further testing of affected and unaffected relatives was recommended to enhance the evidence for pathogenicity. Discussion: This case is an exemplar to illustrate that genomic sequencing yields variants requiring extensive further evaluation. Correct interpretation is essential for medical management e.g. recurrence risks in future pregnancies and prenatal diagnosis. Genomic testing can be extremely powerful, but our experience illustrates the meticulous and labour intensive process necessary to correctly determine the importance of specific genomic variants in disease aetiology. If the potential of this technology is to be realised, significant genomic education is required for those working with patients that have rare genetic diseases.